(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article "Ethical and Legal Aspects of Dictionaries in English Lexicography" delves into the complex challenges faced by lexicographers in the digital and multicultural era. It examines ethical responsibilities such as inclusivity, fairness, and unbiased representation of diverse linguistic and cultural communities, alongside contentious issues like the inclusion of offensive or controversial terms. The legal dimensions are explored in the context of copyright protection, intellectual property rights, trademarks, and the rise of digital and user-generated dictionaries. The paper highlights the evolving role of artificial intelligence and corpus linguistics in addressing these issues while proposing best practices for ethical lexicography and robust legal frameworks. The article serves as a vital reference for understanding the intersection of linguistic scholarship, societal values, and legal constraints in